The influence of US dollar funding conditions on Asian financial markets - Junkyu Lee; Peter Rosenkranz; Arief Ramayandi; Hoang Pham (Asian Development Bank (ADB), 2021)
More than 20 years after the Asian financial crisis, the region's continued high reliance on United States (US) dollar-denominated funding has significant implications for the transmission of global financial conditions to domestic financial and macroeconomic circumstances. Given limited domestic capital market-based financing solutions, a high reliance on funding denominated in US dollars renders countries vulnerable to changing global financial and liquidity conditions. Using a dynamic panel and a vector autoregression model to assess the exchange rate as a possible transmission channel, we find that changes in bilateral US dollar exchange rates can have a significant impact on sovereign credit risk. In particular, a depreciation of the domestic currency against the US dollar leads to a widening of the sovereign bond spread. This finding suggests a significant relationship between US dollar funding exposure, US dollar liquidity conditions, and domestic financial conditions in some emerging Asian economies, and thus highlights one source of structural vulnerability. Given that the magnitude of the effects varies across countries, policy makers need to monitor closely the interplay between the exchange rates and local financial market conditions with tailored prescriptions for domestic financial resilience.
Keywords: F15; F31; F62; F65; G12; G15; 330; bond spread; emerging Asian economies; exchange rate; US dollar funding conditions